The importance of New Product Development (NPD) in contributing to the success of Small and Medium Enterprises (SMEs) of food and beverages industries in Peninsular Malaysia / Noorain Mohd Nordin - Mohd Nordin, Noorain (Faculty of Business and Management, 2005)
The contribution of new products to Small and Medium Enterprises (SMEs) has long been acknowledged. Yet, while an increasing amount of research into New Product Development (NPD) is being carried out in large corporations, similar research activity has not been undertaken in SMEs. As a result very little is known about the impact of NPD on SMEs' competitiveness and the chosen factors that influence their successful development. Focusing on Malaysian food and beverages companies in the SMEs category. this study attempts to bridge this knowledge gap by providing empirical evidence on NPD practices and its success determinants. This study. thus have the following objectives: 1. To determine the important characteristics of NPD in the success of SMEs. 2. To determine the important external environment that influences NPD in the success of SMEs. 3. To determine the important barriers of NPD in the success of SMEs. The fieldwork for this research was carried out in Peninsular Malaysia. Data collected from a "drop-off pick-up" technique of 230 Malaysian food and beverages manufacturing companies demonstrates that while these manufacturers are relatively new to NPD. SMEs tend to suffer from a lack of resources especially in manpower, financing and technology. Though they recognize the importance of introducing new products, new product development is not being exploited strategically. The findings also identify several distinctive factors associated with new product success, which are similar to those found in Western literature. These are: unique and technologically innovative products, skills and competencies, adequate production resources, skills and knowledge, efficient product launching, and a strategic focus. Overall this study provides evidence in support of the NPD model developed in industrialized countries and its applicability within the context of one industrializing country, i.e Peninsular Malaysia. It is recommended that further research be undertaken to test the validity of this model in other industrializing countries.